A contribuição de Henri-Alexandre Junod sobre o avunculado no debate com Radcliffe-Brown - Gajanigo, Paulo (Revista de Antropologia, 2013)
In this article, we revisit the debate between Radcliffe-Brown and Henri-Alexandre Junod. Along with the study of the not very well known Junod’s ethnography, we criticize the unilateral point of view of Junod as a representation of the pseudoscientific method of “conjectural history” –Radcliffe-Brown’s position in his article “The Mother’s Brother in South Africa”. We do not deny this aspect, but we explore Junod’s analysis of tsonga kinship system as a whole, with special attention to the lobolo system. This system requires a different focus of analysis from the lineage system, therefore, we affirm that Junod’s view can be used as a critic of Radcliffe-Brown structural-functionalist approach. We conclude that this debate should not be read as a pure victory of structural-functionalism against the remains of evolutionist methods, moreover should be seen as expression of issues present in the anthropology kinship studies in XX century: kinship’s bilaterally, affinity and reciprocity.